Antimicrobe activity of empty bunches of palm tree’s liquid smoke against Sclerotium rolfsii Sacc. and Puccinia arachidis Speg. 1884 - Pratiwi, Rizky Nomi; Tondok, Efi Toding; Damayanti, Tri Asmira (Universitas Trunojoyo Madura, 2025)
Groundnut (Arachis hypogaea L.) is one of the food crops that has high economic value. However, one of the constraints to groundnut production is the stem base rot (Sclerotium rolfsii) and rust (Puccinia arachidis) diseases. Liquid smoke is known to have antimicrobial activities that need to be further studied for their potential to control various types of pathogens. This study aimed to test the ability of liquid smoke from empty palm bunches in controlling S. rolfsii and P. arachidis in vitro. The phytotoxicity of liquid smoke to seeds was tested using a rolled paper test established in plastic. Antimicrobial activity was tested by using the poisoning medium method against S. rolfsii, while spore germination test against P. arachidis was conducted by direct liquid smoke dripping onto uredospore on object glass. Antimicrobial activity of liquid smoke at concentrations of 0.1%, 0.5%, 1.0%, 1.2%, and 1.4% showed growth inhibition of S. rolfsii by 2.0%, 5.4%, 35.0%, 78.8%, and 100%, respectively. At 24 hours after treatment, the effect of liquid smoke on P. arachidis spore germination at concentrations of 0.1% and 1.0% was 1.7% and 0.0% when compared to the control, 8.4%, and at 48 hours after treatment was 1.5% and 0.0% compared to the control, 9.7%. It indicates the ability of liquid smoke as an antifungal.